KELAYAKAN FLASHCARD MATERI KEANEKARAGAMAN HAYATI BERDASARKAN KANDUNGAN GIZI BUAH KANCING BAJU, KETIPAN, TAMANG HUTAN - Anindya, Dinda; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to test the feasibility of flashcards on the material of various levels of the biodiversity of Indonesia class X. The research methode was descriptive. The flashcard contained material of various levels of the biodiversity of Indonesia class X including the information of the fruits of kancing baju (Etlingera elatior) ketipan (lansium parasiticum) dan tamang hutan (Ardisia pterocaulis). Flashcard  was evaluated by five validators and used Lawshe method. The questioner consisted of 12 criteria with six aspects. The scores CVR and CVI were 0.99. It indicated the feasibility of flashcards was categorized valid and can be used as learning media for material of various levels of biodiversity of Indonesia.           Keywords: Flashcard, rare fruits, Biodiversity.